Implementasi Visi Dan Misi Tk Dharma Wanita Persatuan Sentul Dalam Mencapai Pendidikan Unggul Melalui Budaya Organisasi - Erika Navi Mariani; Diah Ayu Sanggarwati (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Early childhood education or kindergarten plays an important role in forming the foundation for children's holistic development. A clear vision dan mission are the keys to directing cheerful dan motivating learning for children. This research aims to understdan how the integration of vision dan mission with organizational culture can support the achievement of superior education in kindergarten. Qualitative methods were used to collect data based on observation, document analysis dan interviews. The results show that the vision dan mission are reflected in daily practice, dan teachers, principals dan parents play an important role in supporting its implementation. An organizational culture based on the values of cooperation dan honesty strengthens the involvement of all community members. Despite facing challenges, a collaborative approach is able to overcome them. Thus, the implementation of the Dharma Wanita Persatuan Sentul Kindergarten vision dan mission is effective in achieving superior education through a strong organizational culture. Researchers suggest to Dharma Wanita Persatuan Sentul Kindergarten to strengthen the role of teachers, principals dan parents dan implement a routine evaluation system to improve the quality of education.